Induced Mutations in Horsegram: Mutagenic Efficiency and Effectiveness - M. A. Kare2 and A. S. Bhuktar3, R. K. Shirsat1, M. N. Mohrir2 (Recent Research in Science and Technology, 2010)
Abstract Mutation breeding is one of the most reliable techniques in improving crop plants. Physical and chemical mutagens are used to bring the variability. Among chemical mutagens, to identify the efficient mutagen that can bring broad spectrum of variability, it is therefore necessary to study the efficiency and effectiveness of various mutagens. In present study, two varieties of horsegram, viz., SINA (K-42) and KS-2 were treated with three concentrations of ethyl methane sulphonate (EMS), N- nitroso N- ethyl urea (NEU) and sodium azide (SA). Identification of effective mutagen could be possible by studying different parameters. In M2 generation studies were made on the mutagenic efficiency, mutagenic effectiveness and mutagenic rate. In the present study, the results revealed that efficiency of mutagens was variable, sodium azide was most effective mutagen and showed highest mutagenic rate. Keywords: Sodium azide, Mutation, Efficiency, Effectiveness, Mutagenic rate